French Interlingual Interference In The English Compositions Of Algerian Pupils - Gouider , Ilyes (The Journal of Studies in Language, Culture, and Society, 2025)
The present research paper explores the cross-linguistic negative impact of French displayed in the English written compositions of Algerian learners. It identifies the types of interlingual errors resulting from French and attempts to trace their origins to understand their underlying causes. The objective is to address the research gap embodied in unravelling the nature of L2 influence on L3 acquisition and to move beyond the usual scope concerned with the influence of the mother tongue (L1) on newly acquired languages. The examined corpus, comprised of 98 texts written by fourth-year middle school pupils from Algeria, was analysed primarily through the application of error analysis techniques. The categorisation of data involved the use of thematic analysis principles and the inferred interpretations were derived in light of contrastive analysis. The results determined the presence of three types of errors in learners’ writings: lexical-semantic, grammatical and orthographic errors. Lexical errors involved the use of French vocabulary (code-switching/ pseudo-loans) and false cognates, while grammatical errors were embodied in the incorporation of faulty word order, addition of unnecessary articles, dropping the infinitive marker, omission of particles with phrasal verbs, and misuse of prepositions. Two types of orthographic errors related to the writing system of French were identified: spelling and capitalisation errors. Further research is still needed to fathom the interplay between the two languages and the mechanisms that govern cross-linguistic transfer within the Algerian multilingual context of education.